Po267 Exploring the targeted application of TDCS after TBI. (1st December 2017) - Li, Lucia; Violante, Ines; Zimmerman, Karl; Ross, Ewan; Leech, Robert; Hampshire, Adam; Carmichae, David; Sharp, David
Abstract : Introduction: Traumatic brain injury (TBI) disrupts salience (SN) and default mode brain network (DMN) function, causing dysexecutive problems. A possible treatment is to modulate network function using transcranial direct current stimulation (tDCS). Objective: To investigate the effects of tDCS on network and cognitive function after TBI. Methods: 26 healthy subjects and 15 TBI patients underwent simultaneous MRI-tDCS. They performed the Stop Signal Task (SST) under sham, anodal tDCS or cathodal tDCS of the right inferior frontal gyrus (rIFG). Results: Patients had damage to structural connexions within the SN, associated with abnormal DMN activity. rIFG TDCS modulated SN and DMN activity and functional connectivity in a polarity dependent way. An overall effect of stimulation on SST performance was not seen. However, behavioural improvements were seen with anodal stimulation that depended on the network structural integrity. Across all subjects, higher SN structural integrity was associated with improved SST performance during anodal stimulation. Conclusions: Our results show that rIFG tDCS modulates SN and DMN function in a polarity dependent manner. The effects of stimulation interact with network structural integrity. This suggests that an understanding the pattern of axonal injury will be important for achieving beneficial behavioural effects of tDCS following TBI.